A CFD-DEM study of hydrodynamics with heat transfer in a gas-solid fluidized bed reactor for solar thermal applications. (January 2018) - Bellan, Selvan; Matsubara, Koji; Cho, Hyun Seok; Gokon, Nobuyuki; Kodama, Tatsuya
Highlights: A coupled CFD-DEM numerical model has been developed for two-tower solar thermochemical reactor. Presents an experimental visualization of particles circulation pattern and mixing. Presents hydrodynamics and heat transfer characteristics of bubbling fluidized bed. Presents influence of gas flow rate and bed mass on the flow pattern, void fraction and velocity of the particles. Abstract: The particles flow and heat transfer characteristics of a high temperature solar thermochemical fluidized bed reactor have been studied for solar beam-down concentrating systems. A numerical model has been developed by the combined approach of computational fluid dynamics (CFD) and discrete element method (DEM) collisional model since it is an effective approach for studying the gas-solid flow. The discrete ordinate model has been used to solve the radiation heat transfer. An experimental visualization of particles circulation pattern and mixing of two-tower fluidized bed system has been presented. A good agreement has been found between the experimental measurements and numerical predictions. The effect of gas superficial velocity, bed mass and inlet gas temperature on the flow pattern and temperature characteristics of the bed have been investigated. The results showed that the maximum and average temperature of the bed, depends on the top layer position and focal point of the concentrated radiation, decreased when increasing the total mass of the bed.